2018
DOI: 10.1089/dia.2017.0424
|View full text |Cite
|
Sign up to set email alerts
|

Fully Closed-Loop Multiple Model Probabilistic Predictive Controller Artificial Pancreas Performance in Adolescents and Adults in a Supervised Hotel Setting

Abstract: MMPPC was safe in a supervised setting despite meal and exercise challenges. Further studies are needed in a less supervised environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 52 publications
(73 reference statements)
3
40
0
4
Order By: Relevance
“…Use of automated insulin delivery systems have been shown to reduce nocturnal hypoglycemia following physical activity occurring in the afternoon and increase TIR as compared to open‐loop therapy . Yet, the ability to mitigate hypoglycemia during exercise has remained elusive leading to the development of different system announcements, incorporation of heart rate data, dual hormone approaches, and intake of carbohydrates being applied to overcome this obstacle …”
Section: Closed Loop Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of automated insulin delivery systems have been shown to reduce nocturnal hypoglycemia following physical activity occurring in the afternoon and increase TIR as compared to open‐loop therapy . Yet, the ability to mitigate hypoglycemia during exercise has remained elusive leading to the development of different system announcements, incorporation of heart rate data, dual hormone approaches, and intake of carbohydrates being applied to overcome this obstacle …”
Section: Closed Loop Systemsmentioning
confidence: 99%
“…222,249 Yet, the ability to mitigate hypoglycemia during exercise has remained elusive leading to the development of different system announcements, incorporation of heart rate data, dual hormone approaches, and intake of carbohydrates being applied to overcome this obstacle. 214,[250][251][252][253] High user acceptability and improved measures of treatment satisfaction have been shown. [254][255][256][257] However, it should be noted that device alerts and alarms and technical difficulties can negatively affect the overall experience using automated insulin delivery.…”
Section: Free Living Assessments Of Automated Insulin Deliverymentioning
confidence: 99%
“…1) [9093]. A fully closed loop system would automate all insulin delivery including basal insulin and bolus requirements for meals without requiring any user interaction [9, 94]. No fully closed loop system is commercially available, though several designs have undergone preliminary testing [94].…”
Section: Overview Of Ap Systemsmentioning
confidence: 99%
“…A fully closed loop system would automate all insulin delivery including basal insulin and bolus requirements for meals without requiring any user interaction [9, 94]. No fully closed loop system is commercially available, though several designs have undergone preliminary testing [94]. Current AP systems are considered hybrid closed-loop systems, as they involve automation of basal insulin delivery, but still require user input of carbohydrate consumption and delivery of manual insulin boluses for meals [17].…”
Section: Overview Of Ap Systemsmentioning
confidence: 99%
“…Like the many implementations of PID variants, numerous MPC algorithms have been reported that attempt to leverage new or existing MPC techniques to improve the compatibility of these algorithms with the requirements and constraints of diabetes treatment [82]. Among the more recent developments in artificial pancreas systems are the extended [119], multiple model [82], [94], [120], run-to-run tuning [82], [121], zone [122], [123] and periodic-zone [124], event-triggered [125], and velocity-weighted & velocity-penalized [126] MPC algorithms. Each method of MPC attempts to overcome one or more of the challenges discussed previously including practical/safety restrictions [127], interpatient variability, intrapatient variability, and unannounced disturbances such as meals or exercise.…”
Section: Automated Therapy For Diabetesmentioning
confidence: 99%